2020
DOI: 10.1016/j.yebeh.2020.107238
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy self-management during a pandemic: Experiences of people with epilepsy

Abstract: The purpose of this descriptive study was to, from the perspective of adult people with epilepsy (PWE) and caregivers of PWE, explore the effects of the current pandemic and resulting societal changes on epilepsy selfmanagement. Ninety-four respondents completed a mixed-methods quantitative and qualitative survey focused on their epilepsy self-management experiences during the coronavirus disease-19 (COVID-19) pandemic. Respondents noted significant disruption in epilepsy self-management. Lack of ability to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 12 publications
6
65
1
1
Order By: Relevance
“…This is an interesting finding, which could represent a spontaneous fluctuation for some patients, but also indicates that a certain beneficial effect of confinement measures could exist in some particular cases, in terms of schedule and lifestyle regularity and reduction in work stress. However, this small number of patients does not allow making assumptions in this matter, and the negative impact seems to prevail in the overall population of our study, in line with recent literature 25 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is an interesting finding, which could represent a spontaneous fluctuation for some patients, but also indicates that a certain beneficial effect of confinement measures could exist in some particular cases, in terms of schedule and lifestyle regularity and reduction in work stress. However, this small number of patients does not allow making assumptions in this matter, and the negative impact seems to prevail in the overall population of our study, in line with recent literature 25 …”
Section: Discussionsupporting
confidence: 78%
“…However, this small number of patients does not allow making assumptions in this matter, and the negative impact seems to prevail in the overall population of our study, in line with recent literature. 25 The presence of three or more of the risk factors identified here elevated the risk of a seizure frequency increase to 40%, and to our knowledge, no further data related to this issue are available. These findings might be useful to identify the most vulnerable patients in this particular setting who could require closer monitoring.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, in another study, among 5700 PWE, who were managed at the studied centers, only 14 people tested positive for SARS-CoV-2, without obvious impacts on their epilepsy [18]. Six surveys of PWE showed that many people perceived significant disruption in the quality and availability of care to them (31 to 95%), as well as increased stress and social isolation, and increase in seizure frequency (6 to 35%) since the onset of the pandemic [11,12,[14][15][16][17]. One observational comparative study confirmed that PWE showed more psychological distress than healthy controls, and they spent significantly more time following the COVID-19 outbreak news [13].…”
Section: Resultsmentioning
confidence: 98%
“…We enjoyed reading the recent article entitled, “Epilepsy self-management during a pandemic: Experiences of people with epilepsy” by Miller and colleagues published in your esteemed journal [ 1 ]. Although these data are extremely interesting, we have to be very careful when discussing them.…”
mentioning
confidence: 99%
“…Furthermore, it has been suggested that for patients with severe or critical illness, besides the respiratory supportive treatment, a more careful assessment and the treatment of various affected organs are important [ 6 ]. Thus, the neurological implications of SARS-CoV-2 infection have received special attention [ 3 ], and neuroscientists have established consensus recommendations on how to provide the best possible care for people with epilepsy during the novel coronavirus 2019 era [ 1 , [7] , [8] , [9] , [10] ]. In this context, although the medical team's first reaction was to limit access to clinics and neurological centers to preserve patients with epilepsy from being infected [ 10 ], some interesting proposals regarding healthcare facilities logistics, medical procedures and treatment (ensuring a regular supply of antiepileptic drugs), and telemedicine have also been discussed among various epileptologists operating in different regions of the world [ 4 , [7] , [8] , [9] , [10] , [11] ].…”
mentioning
confidence: 99%